The Influence of Digital Competency and Leadership on Employee Performance with Job Satisfaction as A Mediation Variable in Bpsdm Office of The Ministry of Communication and Digital - Widyastuti, Ratna; Trang, Irvan; Taroreh, Rita N. (Abdurrauf Science and Society, 2025)
This study investigates the effect of digital competence and leadership on employee performance, with job satisfaction as a mediating variable, within the Human Resources Development Agency (BPSDM) of the Ministry of Communication and Digital. The research is motivated by the demands of digital transformation in public bureaucracy, requiring employees to possess digital skills and be guided by adaptive leaders. Although employee performance at BPSDM has shown improvement over the past five years, issues remain regarding the effective use of technology and leadership quality. Job satisfaction is also considered a potential mediating factor linking competence and leadership with performance outcomes. A quantitative approach was used, testing seven hypotheses through path analysis. The findings reveal that digital competence has no significant impact on job satisfaction or employee performance. Similarly, leadership does not significantly influence performance but has a strong effect on job satisfaction. Job satisfaction itself does not significantly affect performance and fails to mediate the relationship between digital competence or leadership and employee performance. Out of the seven hypotheses proposed, only one was accepted: leadership significantly influences job satisfaction. These results imply that while leadership can foster job satisfaction, it is not sufficient to enhance employee performance directly or indirectly. Furthermore, digital competence has not yet become a key factor in improving performance or satisfaction in this context. This study contributes to the understanding of how human resource variables interact in public organizations undergoing digital change and provides insight for policymakers aiming to improve performance through leadership and digital skill development.